Customer Value Creation in Multichannel Systems: The Interactive Effect of Integration Quality and Multichannel Complexity. (May 2017) - Kabadayi, Sertan; Loureiro, Yuliya Komarova; Carnevale, Marina
Abstract: This research examines factors that influence consumer perceptions of value created by a multichannel system of service delivery. The literature suggests that multichannel integration quality allows firms to benefit from the effect of synergy and complementarity between channels. We investigate the perceived value of multichannel service delivery in the context of retail banking services, where such multichannel systems are omnipresent. We propose and test a model in which multichannel integration quality is an important value driver, such that higher multichannel integration quality leads to greater value perceptions of not only the multichannel system, but also the overall value of the bank as perceived by the customer. Importantly, the complexity of the multichannel system of service delivery, as perceived by customers, moderates the direct effect of channel integration quality on perceived value of the multichannel system, so that in highly complex multichannel systems, channel integration quality will have a stronger effect on the perceived value to customer. Our findings also shed light on the specific factors that contribute to consumer value perceptions of multichannel retail banking services, which has important implications to managers and researchers.